The Dawn of Single Material Organic Solar Cells - Roncali, Jean; Grosu, Ion (Advanced science, 2019)
Single material organic solar cells (SMOSCs) are based on ambivalent materials containing electron donor (D) and acceptor (A) units capable to ensure the basic functions of light absorption, exciton dissociation, and charge transport. Compared to bicomponent bulk heterojunctions, SMOSCs present several major advantages such as considerable simplification of cell fabrication and a strong stabilization of the morphology of the D/A interface, and thus of the cell lifetime. In addition to these technical issues, SMOSCs pose fundamental questions regarding the possible formation, and dissociation of excitons on the same molecular D–A architecture. SMOSCs are developed with various approaches, namely “double‐cable” polymers, block copolymers, oligomers, and molecules that differ by the donor platform: polymer or molecule, the nature of A, the D–A connection, and the intra‐ and intermolecular interactions of D and A. Although for several years the maximum efficiency of SMOSCs has remained limited to 1.0–1.5%, impressive progress has been recently accomplished leading to SMOSCs with 4.0–5.0% efficiency. Here, recent advances in the synthesis of D–A materials for SMOSCs are presented in the broader context of the chemistry of organic photovoltaic materials in order to discuss possible directions for future research. Single material organic solar cells (SMOSCs) based on ambivalent donor acceptor materials are the ultimate stage of simplification of organic solar cells and a possible solution to the instability of multicomponent cells. Impressive progress in both polymeric and molecular SMOSCs has been recently reported and the related perspectives and fundamental issues are critically discussed here.